(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This thesis provides detailed information on the importance of the use of syntactic-stylistic tools in speech studied in linguistics, asyndeton and polysindeton from their special syntactic devices that help to increase the emotionality of speech. Structural-semantic types of these styles are analyzed in English and Uzbek by giving examples in two languages, and their use in speech is explained by comparing examples in English and Uzbek and similarities and differences in the two languages.